2014
DOI: 10.22555/joeed.v1i1.14
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Education at Primary Level: Reality or Phantasm

Abstract: The objectives of this study were to assess the impacts of Inclusive Education (IE) Project implemented in government schools of Islamabad and anticipate its practicability for public schools. Quantitative and qualitative methods were applied for data collection. Study instruments were structured interviews, unstructured focus group discussions, and questionnaire. The study revealed that Students with Disabilities (SWDs) carrypositive attitudes about their mainstreaming and promote friendships among them. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…It is also reported that there is a lack of preparation among teachers responsible for teaching children with disabilities in both inclusive and non-inclusive schools (Shaukat and Rasheed, 2015). Despite supporting inclusive educational settings, Khan and Behlol (2014) found that teachers lack confidence about teaching children with disabilities, finding appropriate resources, and managing their classrooms. Therefore, it is very relevant to know the relationship between teachers' sense of self-efficacy and their attitude toward behavioral disorders, as it helps to determine the role of teachers' selfawareness in promoting inclusive education of children with behavioral disorders (Ghosh, 2022).…”
Section: Teachers' Sense Of Self-efficacymentioning
confidence: 99%
“…It is also reported that there is a lack of preparation among teachers responsible for teaching children with disabilities in both inclusive and non-inclusive schools (Shaukat and Rasheed, 2015). Despite supporting inclusive educational settings, Khan and Behlol (2014) found that teachers lack confidence about teaching children with disabilities, finding appropriate resources, and managing their classrooms. Therefore, it is very relevant to know the relationship between teachers' sense of self-efficacy and their attitude toward behavioral disorders, as it helps to determine the role of teachers' selfawareness in promoting inclusive education of children with behavioral disorders (Ghosh, 2022).…”
Section: Teachers' Sense Of Self-efficacymentioning
confidence: 99%
“…Vol. 33, No.3, 2022; doi 10.47985/dcidj.539 disabilities, using appropriate resources and managing classrooms (Khan & Behlol, 2014). Therefore, it is very important to know the relationship between teachers' sense of self-efficacy and their opinions, as it helps to determine the role of teachers' self-awareness in promoting inclusive education (Ghosh, 2022).…”
Section: Letter To Editormentioning
confidence: 99%
“…In Pakistan, as pointed out by Khan and Behlol (2014), teachers and school management have a positive attitude towards the inclusion of students with educational needs; nevertheless, they face certain challenges when it comes to the practical implementation of inclusive education. Similarly, awareness regarding the importance of parental involvement to promote inclusive education in Pakistan seems to be an uncovered area.…”
Section: Introductionmentioning
confidence: 99%